Analysis the Integrated Learning (Listening and Speaking) on Podcast “Effortless English Program” by AJ. Hoge - Muzaqi, Ahmad Imam (Jurnal Pendidikan, Sains Dan Teknologi, 2025)
Speaking skills currently require serious approaches to be learned together. Through the combined language skill integrating with listening skills, it is certainly relevant to improve communicative abilities. This study aims to explore integrated language skill techniques, particularly combining speaking and listening, to enhance communicative abilities in learners within the “Effortless English Program” by AJ. Hoge. This study utilized a qualitative descriptive design with content analysis. Data were collected from a sample of 37 out of 255 episodes of A.J. Hoge’s Effortless English Podcast, featuring Hoge’s broadcasts and discussions among English club members. The findings showed the Effortless English Program applied six key techniques in the Effortless English Program, such as (1) TPR Storytelling, (2) Listen and Answer, (3) Point of View Mini Story, (4) Simultaneous Listening and Reading, (5) Repetitive Listening and Speaking, and (6) Listen to Movie, significantly aided learners in developing speaking skills. This integrated approach is recommended as a practical alternative for formal or informal English instruction at various proficiency levels and ages. These techniques hopefully should be alternative strategies and new concepts reviewed by teachers and applied for students/learners in classroom activity.